PERSEPSI PERAWAT PERKESMAS TENTANG PERAN PERAWAT SEBAGAI EDUKATOR DI PUSKESMAS SE-KOTA PEKANBARU - Andini, Vici (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Public Health Nursing (PHN) is a combination of the nursing and public health sciences, which is giving priority to preventive and promotif sevices, without neglecting curative and rehabilitative services. The main implementer of PHN activities in public health center is PHN nurses. Nurses in carrying out the activities PHN nurses is strongly influenced by the perception of nurses about the role of nurse. PHN nurses have at least 6 main roles, one of which is an educator. As an educator, PHN nurse need to explain the concepts and facts about health, demonstrated health care and maintenance procedures, improve client’s health behavior, and evaluate client progress in learning. The purpose of the study is to identify the perception of PHN nurses about the roles of nurses as an educators in the public health center in Pekanbaru. This research uses descriptive design that is conducted in all public health center in Pekanbaru. The sampling technique used is proportional random sampling technique, involving 120 respondents. Instrument used is questionnaire that has been tested for validity and reliability. Analysis test used is univariate analysis with the results show 91.7% respondents agree to explained the concepts and facts about health, 92.5% respondents agree to demonstrate health care and maintenance procedures, 90.8% respondents agree to participated in improving client’s health behaviors and 89.2% respondents agree to evaluated client progress in learning. The conclusion of this study is the perception of PHN nurses about the role of nurses as an educator is already good. Based on this result, it is recommended to nurses in public health center to implement the role of nurse as an educator appropriate based on perception of PHN nurses about the role of nurse, in order to improve public health optimally.Keywords : Educator, Nurse, Public Health Nursing, Perception